2017
DOI: 10.1016/j.cemconcomp.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Early age fracture properties of microstructurally-designed mortars

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
2
2
0
Order By: Relevance
“…However, at low temperatures, the third stage was not seen or was not notable because this study only investigated the age of up to 60 d, meaning that there was a lot of un-hydrated cement inside the concrete under these curing temperatures. This variation of concrete fracture parameters regarding the age was consistent with other independent investigations [34]. For example, Beygi et al [35] found that with the increase of test age from 3 to 90 d, G F and K IC increase from 0.961 MPam 0.5 to 1.448 MPam 0.5 and from 99.7 N•m −1 to 126.5 N•m −1 , respectively.…”
Section: Discussionsupporting
confidence: 89%
“…However, at low temperatures, the third stage was not seen or was not notable because this study only investigated the age of up to 60 d, meaning that there was a lot of un-hydrated cement inside the concrete under these curing temperatures. This variation of concrete fracture parameters regarding the age was consistent with other independent investigations [34]. For example, Beygi et al [35] found that with the increase of test age from 3 to 90 d, G F and K IC increase from 0.961 MPam 0.5 to 1.448 MPam 0.5 and from 99.7 N•m −1 to 126.5 N•m −1 , respectively.…”
Section: Discussionsupporting
confidence: 89%
“…A negligible effect of the small differences of fineness between the cement and the filler on the mechanical behavior was assumed based on the original work by Termkhajornkit et al [29] who reported that the fineness had minor effect on the relation between hydration degree and porosity. This assumption is confirmed by the good agreement of the strength and elastic properties between the equivalent and real systems reported in the following sections and in the previous studies [30,32].…”
Section: Sem and Isothermal Calorimetry Measurements For MIX Design Osupporting
confidence: 85%
“…In the equivalent system, where all cement has hydrated (and the system is thus inert), the volumetric composition is similar to that in the real system. By using this approach, a static (non-aging) system is obtained that is capable of emulating specific characteristics of a real system at the corresponding age, e.g., porosity, strength, elastic properties, fracture properties [30,32,33]. Equivalent systems have been also used in [34] for assessing drying shrinkage of mortars at early ages.…”
Section: Introductionmentioning
confidence: 99%
“…These numerical results were successively confirmed in experiments with limestone filler [29,31] . Recently, similar considerations allowed to develop static equivalent systems to study hydration-related early-age properties, shrinkage and creep, by substituting parts of the cement with inert quartz filler [32][33][34][35]. Based on the previous considerations, it can be assumed that in general the production of low clinker high performance concretes (LCHPCs) should be possible and that these mixtures could contribute to reduce the CO 2 emissions.…”
Section: Introductionmentioning
confidence: 99%